A low switching loss GaN trench MOSFET design utilizing a triple-shield structure - Yihang Qiu; Li Wei (Scientific Reports)
Abstract An innovative GaN trench MOSFET featuring an ultra-low gate-drain charge (Q gd ) is proposed, with its operational mechanisms thoroughly investigated using TCAD simulations. This novel MOSFET design introduces a triple-shield structure (BPSG-MOS) comprising three critical components: (1) a grounded split gate (SG), (2) a P+ shield region (PSR), and (3) a semi-wrapped BP layer that extends the P-shield beneath the gate and along the sidewalls of the trench gate. Both the SG and PSR effectively reduce gate-drain coupling, transforming most of the gate-drain capacitance (C gd ) into a series combination of gate-source capacitance (C gs ) and drain-source capacitance (C ds ). Furthermore, the BP layer refines the gate-drain capacitance by converting the C gd at the trench gate sidewalls into C gs . This configuration significantly lowers C gd , resulting in an ultra-low Q gd . Compared to the dual-shield MOSFET (PSGT-MOS) and the conventional trench MOSFET (TG-MOS), the BPSG-MOS achieves reductions in C gd by 81% and 98%, respectively.